APLIKASI SISTEM PENGADUAN MASYARAKAT DI PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK (P2TP2A) PROVINSI BANTEN - Syaechurodji Syaechurodji; Anju Parapat (Journal of Innovation And Future Technology (IFTECH), 2019)
This research is based on community service complaints about cases of violence and trafficking by the Integrated Service Center for Women and Children Empowerment in Banten Province. This service provided by this institution still uses the system directly, in this case it does not use an online system. So it does not provide an opportunity for people who cannot come directly to report their cases to P2TP2A Banten Province. This problem makes it difficult for people to get these services. The process model of the public complaints system application software in Banten Province P2TP2A used is the Waterfall model. This model is used to find out the steps needed to design this application.The application of the Community complaints system in P2TP2A Province makes the community able to obtain responses more quickly and effectively. The application of the Community complaints system in P2TP2A Province is a facility that can connect the community with P2TP2A Banten Province because it can be accessed at any place and time at any time. With this application, data related to acts of violence in Banten Province can be obtained accurately, in detail and efficiently.